Collaboratives to improve industrial maintenance contract relationships. Issue 4 (2nd October 2019) - De Jong, Arjan; Smit, Klaas
Abstract : Purpose: The purpose of this paper is to demonstrate how collaborative contracts can improve industrial maintenance contract relationships. Design/methodology/approach: The research compares performance contracts with collaborative contracts, a new contract type whereby the contract parties align their objectives. The study uses game theory and describes the contract types as mechanism designs to compare the contract types. The mechanisms are validated with case studies. The utility of the contract types is verified with Monte Carlo simulations using expert opinions. Findings: The research demonstrates that, under certain conditions, collaborative contracts result in a higher utility than performance contracts for all contract parties. Practical implications: The use of collaborative contracts between an operator of a technical system and a maintenance organisation reduces maintenance costs and improves the availability of the technical system, increasing the utility for all contract parties. Originality/value: The collaborative contract is a new contract type for maintenance services and the research method provides a new approach to optimise industrial maintenance contract relationships.